PENGARUH WAKTU PENYIMPANAN BENIH DAN KONSENTRASI LARUTAN ASAM SULFAT TERHADAP PERTUMBUHAN BENIH JARAK (Jatropha curcas Linn.) DI PERSEMAIAN - Kovertina Rakhmi Indriana; R Budiasih (Jurnal Agroekoteknologi, 2016)
The aims of the research were to study the growth of plants in the nursery and look for the optimum concentration of H2SO4 solution at certain storage duration that gives the highest dry plant weight in the nursery. Experiments were conducted in the seed laboratory and in the nursery of Faculty of Agriculture, Winaya Mukti University using randomized block design factorial with 2 factors. The first factor was the time and concentration of sulfuric acid solution i.e. Soaking 6 minutes in H2SO4 0.25%, 0.50%, 0.75% and 1.0%. The second factor was seed storage duration i.e. without being stored, 1, 2, and 3 months. The data was analized using linear quadratic regression method. The experimental results showed that there was interaction between seed storage time and concentration of sulfuric acid solution on leaf area and plant dry weight. The treatment without storage time and concentration of 0.75% sulfuric acid solution gave the best effect compared to other treatments. Zero minutes of storage followed with sulfuric acid concentration as much as 0.67% gave the highest dry plant weight of 28.193 g.Key words: Jarak seed, Concentration H2SO4, Seed saving time